Latin Vulgate, Bible Book Titles and Names - Anonymous (Salt Lake City, UT : Project Gutenberg, 1997)
"Latin Vulgate, Bible Book Titles and Names" by Anonymous is a reference list documenting the structure of the Latin Vulgate Bible. This work catalogs the 76 books of the Clementine Vulgate edition, comparing their Latin names and numbering systems with English translations like the Douay-Rheims and King James versions. The list addresses variations in book organization, psalm numbering, and apocryphal divisions that often confuse modern readers, while also documenting how different Vulgate editions arrange their contents differently. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Books_of_the_Vulgate
Release date is 1997-02-01
Produced by Dennis McCarthy
Keywords: Bible